The relationship between isokinetic knee extension and flexion strength with soccer kick kinematics: an electromyographic evaluation - Kellis, E.; Katis, A. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The purpose of this study was to investigate the relationship between isokinetic strength knee testing and soccer kick kinematics using electromyography (EMG). Methods: Thirteen pubertal soccer players (age: 14.3±0.4 years) performed maximum instep soccer kicks, while knee angular position of the swinging leg was recorded using a twin-axis electrogoniometer. Bipolar surface EMG activity of the vastus medialis, vastus lateralis and biceps femoris (BF) muscles was recorded. The subjects also performed maximum knee extension and flexion efforts at concentric angular velocities of 1.04, 3.14 and 5.23 rad·s-1 and eccentric angular velocities of 1.04 and 3.14 rad·s-1. Results: The correlation coefficients between isokinetic moments and knee angular velocity values during the kick ranged from 0.609 to 0.898 for concentric moments and from 0.431 to 0.612 for eccentric moments. Agonist EMG values during isokinetic tests ranged from 63.17±19.9% to 128.7±34.9% maximum voluntary contraction (MVC). Antagonist EMG levels ranged from 9.76±6.12% to 36.91±22.81% MVC. The corresponding EMG values during the soccer kick ranged from 12.78±6.8% to 122.34±61.5% MVC and increased as the foot approached the ball. Conclusion: Isokinetic tests at intermediate and fast angular velocities are adequate for monitoring strength training programs in soccer. However, muscle activation patterns differ between the two movements, especially those of the BF muscle.